A Comparative Study on Willingness to Pay for Breast Cancer and Osteoporosis Screening in Kerman, Southeastern Iran - Asma SABERMAHANI; Sedighe MOHAMMAD TAGHIZADE; Reza GOODARZI (Tehran University of Medical Sciences, 2017)
Background: One of the economic evaluation techniques involves calculation of willingness to pay (WTP) for a service to find out the value of that service from the clients' perspective. This study estimated WTP for both breast cancer and osteoporosis screening and comparatively examined the contributing factors. In fact, the comparisons served to provide an exact analysis of individual attitudes and behaviors in relation to screening programs for cancers and other diseases. Methods: This study was first designed in six scenarios several questionnaires concerning individual breast cancer and osteoporosis screening cases, and determined the WTP median in each scenario between people in Kerman Province of Iran in 2016. Then, the demand function for breast cancer and osteoporosis screening was formulated. Moreover, the factors contributing to WTP were examined through various scenarios in Stata and econometric techniques. Results: The median and mean values of WTP in all the above scenarios were greater for breast cancer screening than for osteoporosis screening. Theoretically, the price assumed a minus sign whereas risk assumed a plus sign within the demand function formulated for both screening programs. Regarding the evaluated factors, age in breast cancer screening and risk of disease in osteoporosis screening were the major factors contributing to WTP. Conclusion: Breast cancer screening was more valuable than osteoporosis screening program from the perspective of the subjects. The programs can be successfully designed by concentrating on patients' age groups in breast cancer screening and high-risk patients in osteoporosis screening.